Movement, party and electoral dynamics. Syriza’s electoral success as a movement effect (2010-2015) - Papanikolopoulos, Dimitris; Rongas, Vassilis (Ελληνική Επιθεώρηση Πολιτικής Επιστήμης, 2020)
In this article we approach SYRIZA’s electoral success between 2012 and 2015 as a movement effect. We focus on SYRIZA’s features, strategy and message that have been developed on the grounds of its movement activity, as well as on the external political conditions which SYRIZA seems to take advantage of. We argue that the anti-austerity campaign created the necessary preconditions for the electoral and political rise of SYRIZA, namely the emergence of a new political boundary between pro- and anti-Memorandum forces and a subsequent majoritarian socio-political category that could be transformed into a privileged electoral pool for SYRIZA.